Modeling IT Value based on Meta-Analysis - Suhardi Suhardi; Novianto Budi Kurniawan; Aan Subrata; Jaka Sembiring (IAES Indonesia Section, 2017)
Over the last two decades, research about IT value has been done. The main purpose of IT values research is to determine how IT investment gives impact and value to organization performance. Because of vital role and function of IT, the organization required to understand how IT could create business value. Therefore, an understanding of IT value is needed. Systematic literature review in meta-analysis is required to determine the relationship between IT resources, organization capabilities, organization core competencies, and organization performances. The research was conducted on 53 publications which generate the classification matrix components that have an impact on organization performance. Hypothesis testing results that organization has the best performance on financial, efficiency, and other performance through external capability and core competence. So, indirect effect model is better than direct effect model in explaining IT value.